(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
The primary purpose of this paper is broadly to discuss the normative foundations of peace education in the context of war and peace. This is an exercise others have engaged in with far greater depth and investment, building on the work of scholars before them. While this is the primary purpose of the paper, I will also centrally utilize the narrative lens of W.E.B DuBois as exhibited in his seminal 1903 work The Souls of Black Folks throughout as a contextual framework for the theoretical conversations seen throughout the field of peace education. Snauwaert writes that the peace education is advanced through the development of normative philosophical foundations, yet “philosophical reflection on the normative foundations of peace studies education remains underdeveloped” (Snauwaert, under review).